A HILIC‐MS/MS method for simultaneous quantification of the lysosomal disease markers galactosylsphingosine and glucosylsphingosine in mouse serum. (26th April 2018) - Sidhu, Rohini; Mikulka, Christina R.; Fujiwara, Hideji; Sands, Mark S.; Schaffer, Jean E.; Ory, Daniel S.; Jiang, Xuntian
Abstract: Deficiencies of galactosylceramidase and glucocerebrosidase result in the accumulation of galactosylsphingosine (GalSph) and glucosylsphingosine (GluSph) in Krabbe and Gaucher diseases, respectively. GalSph and GluSph are useful biomarkers for both diagnosis and monitoring of treatment effects. We have developed and validated a sensitive, accurate, high‐throughput assay for simultaneous determination of the concentration of GalSph and GluSph in mouse serum. GalSph and GluSph and their deuterated internal standards were extracted by protein precipitation in quantitative recoveries, baseline separated by hydrophilic interaction chromatography and detected by positive‐ion electrospray mass spectrometry in multiple reaction monitoring mode. Total run time was 7 min. The lower limit of quantification was 0.2 ng/mL for both GalSph and GluSph. Sample stability, assay precision and accuracy, and method robustness were demonstrated. This method has been successfully applied to measurement of these lipid biomarkers in a natural history study in twitcher (Krabbe) mice.